Further in vivo evidence implying DNA apurinic/apyrimidinic endonuclease activity in Trypanosoma cruzi oxidative stress survival. Issue 10 (17th May 2019) - Valenzuela, Lucía; Sepúlveda, Sofía; Bahamondes, Paula; Ramirez‐Toloza, Galia; Galanti, Norbel; Cabrera, Gonzalo
Abstract: Trypanosoma cruzi is under the attack of reactive species produced by its mammalian and insect hosts. To survive, it must repair its damaged DNA. We have shown that a base excision DNA repair (BER)‐specific parasite TcAP1 endonuclease is involved in the resistance to H2 O2 . However, a putative TcAP1 negative dominant form impairing TcAP1 activity in vitro did not show any in vivo effect. Here, we show that a negative dominant form of the human APE1 apurinic/apyrimidinic (AP) endonuclease (hAPE1DN) induces a decrease in epimastigote and metacyclic trypomastigote viability when parasites were exposed to H2 O2 . Those results confirm that TcAP1 AP endonuclease activity plays an important role in epimastigote and in infective metacyclic trypomastigote oxidative DNA damage resistance leading to parasite persistence in the insect and mammalian hosts. All along its biological cycle and in its different cellular forms, T. cruzi, the etiological parasite agent of Chagas' disease, is under the attack of reactive species produced by its mammalian and insect hosts. To survive, T. cruzi must repair their oxidative damaged DNA. We have previously shown that a specific parasite TcAP1 AP endonuclease of the BER is involved in the T. cruzi resistance to oxidative DNA damage. We have also demonstrated that epimastigotes and cell‐derived trypomastigotes parasite forms expressing a putative TcAP1 negative dominant form (that impairs the TcAP1 activity in vitro), did not show any in vivo effect in parasite viability when exposed to oxidative stress. In this work, we show the expression of a negative dominant form of the human APE1 AP endonuclease fused to a green fluorescent protein (GFP; hAPE1DN‐GFP) in T. cruzi epimastigotes. The fusion protein is found both in the nucleus and cytoplasm of noninfective epimastigotes but only in the nucleus in metacyclic and cell‐derived trypomastigote infective forms. Contrarily to the TcAP1 negative dominant form, the ectopic expression of hAPE1DN‐GFP induces a decrease in epimastigote and metacyclic trypomastigote viability when parasites were exposed to increasing H2 O2 concentrations. No such effect was evident in expressing hAPE1DN‐GFP cell‐derived trypomastigotes. Although the viability of both wild‐type infective trypomastigote forms diminishes when parasites are submitted to acute oxidative stress, the metacyclic forms are more resistant to H2 O2 exposure than cell‐derived trypomastigotes.Those results confirm that the BER pathway and particularly the AP endonuclease activity play an important role in epimastigote and metacyclic trypomastigote oxidative DNA damage resistance leading to parasite survival and persistence inside the mammalian and insect host cells. Abstract : 1. Ectopic expression of hAPE1DN‐GFP in T. cruzi parasite forms is located in the nucleus 2. hAPE1DN‐GFP decrease the viability of T. cruzi parasite forms exposed to H2O2 3. AP endonuclease activity plays a role in T. cruzi oxidative DNA damage resistance